METAMORPHISM OF SEDIMENTARY ROCKS AND THEIR DEPOSITIONAL FORMS - Kayumov Odiljon Abduraufovich (Galaxy International Interdisciplinary Research Journal, 2023)
Sedimentary rocks are formed from the accumulation and lithification of sediments such as sand, silt, clay, and organic materials. These rocks undergo metamorphism when subjected to high temperature and pressure conditions. This article explores the metamorphic processes experienced by sedimentary rocks and their deposition forms.